Dysfunctional uterine bleeding in adolescence. - Bachmann Sánchez, Carlos (2015)
The study was conducted in 500 adolescents schoolgirls aged between 9-17 years in order to study dysfunctional bleeding. The age of the respondents and the age of menarche were similar, there were no significant differences. The duration of menses for Lima, Tarma and Tarapoto have been within the limits set by the authors as they progress downward trend cycles. The menstrual interval has been normal for the most part, the characteristic aligomenorrea at this stage was little tendency to decrease as the cycles progress and polymenorrhea and hypermenorrhea have been rare, but medical consultation originated less than 10%.